A Neuromotor Device for Reducing Phantom Limb Pain in Individuals with Spinal Cord Injury - Cui, L.; Astudillo, G.; Allison, Garry (2016)
© The Authors, published by EDP Sciences, 2016. Phantom Limb Pain is a disorder that can be experienced by individuals after amputation or spinal cord injury. In spinal cord injury the paralysis or paresis is often bilateral, thus limiting the application of apparent movement as a therapeutic model for phantom limb pain. This project aimed to develop a robotic rehabilitation device that replicated apparent movement to apply the same therapeutic principles with individuals with lower limb phantom pain that have bilateral paralysis of paresis. The proposed device achieved lower limb planar motion of the knee by a six-bar linkage of a single degree of freedom (DOF). It is driven by a linear actuator while the ankle motion is achieved by a gear motor, reaching an effective 70° range of motion for both joints. The system features closed loop control using feedback from surface electromyography sensors, limit switches and position sensors with an Arduino microcontroller as the control unit. This device will be used to further our understanding of the disorder and create opportunities for robot aided treatment for individuals with phantom limb pain as a result of spinal cord injury.